An Analysis of Phatic Communication Employed of The Character of Will and Louise in Movie Entitle Me Before You - Sahlan Tampubolon; Kammer Tuahman Sipayung; Ulan Susi Manullang (Merwin Publisher, 2023)
This research was conducted to describe the forms and the roles of phatic communion employed by characters in the movie entitled Me Before You. This research used the pragmatic approach. This research was a descriptive qualitative research. The dialogs containing the phatic communion were taken as data. The result of the analysis can be seen as follows: First, there are four forms of phatic communion employed by the characters in the movie entitled Me Before You, namely ritual words that are exchanged when people meet, standard topic of conversation, supportive chat and meaningless word or misunderstood words. The total number of forms of phatic communion are; Ritual words that are exchanged when people meet 3 utterances = 9.00%, Standard Topic of Conversation 11 utterances = 34.37%, Supportive Chat 14 utterances = 43.75%, Meaningless words or even misunderstood words 4 utterances = 12.88%. Second, there are three roles of phatic communion, namely opening phase, middle phase, closing phase. The total number of roles of phatic communion are; Opening phase 3 utterances = 60.00%, Middle phase 1 utterances = 20.00, and Closing phase 11 utterances = 20.00%. Phatic communion occurs both in formal or informal situation and the relationship between the participants can be intimate or distant. It can happen in both higher and lower status. The atmosphere is commonly good but if the atmosphere is bad, phatic communion utterances will help to turn into the good one. The attitude of the participants while uttering phatic communion utterances is usually sympathetic. It can be seen from the low tone. At last, phatic communion functions to establish and maintain social relationship between people in society. Keywords: Pragmatics, Phatic Communion, Me Before You movie.